Effect of foliar application of nano micro nutrients and deficit irrigation on stay green characteristics and drought resistance in maize - Kathirvelan, P; Vaishnavi, S; Manivannan, V; Djanaguiraman, M; Thiyageshwari, S (Plant Science Today, 2025)
The stay-green character is a crucial trait linked to delayed leaf senescence, which enables the plant to continue photosynthetic activity for an extended time under early and terminal drought. Reduced water availability causes early leaf senescence, lower chlorophyll content and eventually poor yield in maize. The objectives were to quantify the effects of irrigation regimes, nanocomposite levels physiological parameters, yield attributes and yield of maize. The main plot treatments comprised of well irrigated and withheld irrigation, while the sub plot treatments consisted of different nanoparticles viz., ZnO, MnO, (ZnO + MnO), TNAU nano revive and ZnSO4 + MnSO4. The results revealed that higher dry matter production (5282 and 9891 kg/ha), leaf nitrogen (44.28 and 39.97), grain filling rate, grain filling duration (34.44 days), green leaf area (92.50%) and proline content (0.59 and 1.28 mg g -1) were recorded at tasseling and grain filling stage, respectively under well-irrigated conditions. Foliar spraying of ZnO (100 ppm) and MnO (20 ppm) nanocomposite, registered higher root biomass (24.21 and 32.11 g/plant), leaf nitrogen (44.6 and 39.1), dry matter production, green leaf area, lowest proline content which ultimately resulted in a higher number of cobs/plant, number of grains row/cob, number of grains/grain row, test weight (1000 grains weight), shelling percentage, crop water use (18.79 kg/ha/mm), grain yield (8.20 t/ha), stover yield (12.2 t/ha) and benefit cost ratio of 2.4. Thus, it could be concluded that well-irrigated condition followed by foliar spray with ZnO (100 ppm) and MnO (20 ppm) registered higher growth, yield attributes, yield, and economics.